ANALYSIS OF OUTPATIENT SATISFACTION IN HEALTH SERVICES - Kurmia Reza Utami; Lina Oktavia; Fera Meliyanti (LPPM STIKES Al-Ma'arif Baturaja, 2025)
The success of health services is largely determined by patient satisfaction. In addition, in 2023, there were 12% of outpatients who were dissatisfied with the services provided at RSUD Lubai Ulu. The purpose of this study was to determine the factors that influence outpatient satisfaction in 2024. This study is observational and uses an analytic survey method with a cross-sectional design. This study had a population of 264 samples and a sample of 88 samples. The results showed that responsiveness p value = 0.001, competence p value = 0.003, communication p value = 0.000, reliability p value = 0.000, and physical evidence p value = 0.113. It is concluded that there is a relationship between the variables of responsiveness, competence, communication, and reliability with patient satisfaction with health services at Lubai Ulu Hospital. However, for the physical evidence variable, no relationship was found with patient satisfaction with health services. RSUD Lubai Ulu can provide training to all staff to improve their ability to meet patient needs quickly and accurately